1994
DOI: 10.3109/00207459408986300
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Risk Factors As Predictors of Developmental Functioning

Abstract: This study examined the relationship between perinatal risk factors and developmental functioning for a referred population of 216 children. A canonical correlation analysis indicated that 31% of the variability in developmental information could be predicted from perinatal events. The results were interpreted as lending support to a multivariate link between perinatal complications and developmental functioning for referred children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The fact that a child has experienced a complication or risk factor does not insure that a negative outcome will ensue. Indeed, the current findings concur with research that has demonstrated greater relationships between perinatal events and poor outcomes when perinatal information is considered collectively (Batchelor, Dean, Gray and Wenck, 1991 ;Gattan, Arceneaux, Dean and Anderson, 1994;Gray, Dean, Strom, Wheeler and Brockley, 1989). However, risk factors and complications rarely appear in isolation; rather, complications generally occur in conjunction with other events.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The fact that a child has experienced a complication or risk factor does not insure that a negative outcome will ensue. Indeed, the current findings concur with research that has demonstrated greater relationships between perinatal events and poor outcomes when perinatal information is considered collectively (Batchelor, Dean, Gray and Wenck, 1991 ;Gattan, Arceneaux, Dean and Anderson, 1994;Gray, Dean, Strom, Wheeler and Brockley, 1989). However, risk factors and complications rarely appear in isolation; rather, complications generally occur in conjunction with other events.…”
Section: Discussionsupporting
confidence: 88%
“…The MPS has been found to distinguish significantly between normal children and those with developmental disability (Gray, Dean, Strom, Wheeler and Brockley, 1989), (attentional disorders (McIntosh, Mulkins and Dean 1995)), autism (Wilkerson, 1992), and emotional/behavioral disorders (Batchelor, Dean, Gray and Wenck, 1991). Other research has shown the MPS to predict both developmental functioning (Gattan, Arceneaux, Dean and Anderson, 1994) and school achievement of children with learning disabilities (Gray, Davis, McCoy, Dean and Joy, 1992).…”
Section: I42mentioning
confidence: 99%
“…The correlation between cerebral palsy and perinatal asphyxia has been questioned. Cerebral palsy occurs in 2.5 of 1000 births, with 10-25% of cases of cerebral palsy associated with perinatal asphyxia (27)(28)(29). The young adults in this study had been selected on being without neurological impairment at a young age.…”
Section: Discussionmentioning
confidence: 99%